T Cell Donor Type Regulator Required to Prevent Failure of Bone Marrow Transplantation of Alogenic System on Model C57BL / 6 → BALB / c - Muhaimin Rifa’i (Natural B, Journal of Health and Environmental Sciences, 2012)
In solid organ and bone marrow transplantation, rejection of donor tissue by recipient and graft versus host disease (GVHD) reactions are the most important issues in the health field. Furthermore, it is known that the tolerance between donor and recipient cannot be maintained for long term without manipulation. To determine the role of regulatory T cells, in this experiment we conducted infusion of donor type CD4+CD25+ T cells. Before transplantation was performed, recipients were irradiated with lethal doses of 850 rad. In this study, we demonstrated that the infusion of donor type CD4+CD25+ regulatory T cells in transplantation model of C57BL/6 → BALB/c promoted the tolerance of recipient against donor. Incontras, conventional T cells CD4+CD25- cannot help the success of transplantation at three months post-transplantation. Rejection of donor tissue by the recipient and GVHD reaction are caused by the activation of T cells and lack of regulatory T cells, CD4+CD25+. These results suggest that CD4+CD25+ regulatory T cells play an important role to homeostasis maintaining and keeping the number and function of lymphocyte T cells in normal circumstances. Furthermore, this study demonstrated that donor CD4+CD25+ regulatory T cellsexpress high levels of Foxp3 molecules.